Nano-encapsulation of Red Beetroot Extract Based on Betalain Using of Complex Coacervation in Gummy Candies - Atfeh Ghorchi; Akram Arianfar; Vahid Hakimzadeh; Sara Naji-Tabasi (مجله پژوهش‌های علوم و صنایع غذایی ایران)
IntroductionRed beet has nutritional and health-promoting properties due to containing bioactive compounds such as phenolic compounds and betanin.  Co-encapsulation of more than one core material in a single encapsulation system may increase the bioactivity of individual components. Customer attitudes and behaviors have moved towards health foods because they have more concerns on increasing environmental stresses such as pollution and toxic substances in the environment. Confectionery products are not exactly foods, but they are widely consumed by children and adults. Traditional gummy confection consists of high amounts of synthetic colorings or flavorings in a gelling agent, commonly known as gelatin, along with acids and sweeteners. Natural color in the form of pigments is synthesized and accumulated in living biological cells of algae, vertebrates, invertebrates, fungi, lichens, or bacteria. The red color in food industry comes mainly from two pigments: anthocyanin and betalains. Among the major groups of natural pigments, betalains can be considered as the least studied, due to its limited sources. The main commercially produced crop  containing betalain is red beet root, however many researchers are exploring red dragon fruit or pitaya as a viable alternative. Betalains, derived from beetroot are water-soluble nitrogenous pigments that stop or delay the oxidation process and exhibit anti-tumor and antiatherosclerotic effects. The application of red color  from beetroot (mainly betalains) is permitted widely in ice cream, sherbet, yogurt, powdered soft drink mix along with confectionaries, soups, and bacon products. The stability of betalains varies with different levels of water activity, temperatures, exposure to oxygen, and light. Complex coacervation is one of the oldest and simplest techniques of encapsulating bioactive compounds for delivery in controlled manner. The technique associates simple preparation conditions, such as non-toxic solvent and low agitation, the techniques has also been employed in the encapsulation of protein and human cells. Microcapsules prepared by complex coacervation are water-insoluble, possessing excellent controlled-release characteristics. Complex coacervation is a technique by which phase separation occurs when oppositely charged polyelectrolytes are electrically balanced in aqueous media. This depends on relatively a set of conditions such as pH, charge density on the polymers, colloid concentration, ionic strength of the medium, temperature, etc. However, all polyelectrolytes do not exhibit this phenomenon.Materials and MethodsThe features of water activity, moisture, acidity, Brix, antioxidant activity, texture characteristics, colorimetry and sensory evaluation of pastilles were investigated. All analyzes were performed with three replications in a completely randomized design. Means were compared using Duncan's multi-range test at a significant level of 5% with SPSS version 22 software.Results and DiscussionThe results showed that water activity of samples containing nanomicrocoating of red beet extract was significantly lower than the control sample (p<0.05), but the moisture, acidity and brix of the sample containing nanomicrocoating of red beet extract were significantly higher from the control (p<0.05). During the storage period of 28 days, it showed that the sample containing 1.5% red beetroot extract's nano-coating had a significantly higher stability of the antioxidant property than other samples (p<0.05). The results of the histological test showed that the sample containing the red beet extract nano-coating had a significant decrease in hardness, stickiness and chewability compared to the control (p<0.05), but the degree of cohesion showed a significant increase (p<0.05). Examining the color parameters of the samples containing red beetroot extract nano-coating compared to the control sample also showed that it caused a decrease in brightness (L*) and yellowness (b*) and an increase in (a*).ConclusionThe results of the sensory evaluation showed that the sample containing 1% red beetroot extract nano-coating  was awarded the highest score compared to the control.